Perceived similarity of desired intimacy in same-sex couples - Schultz-Saindon, Kasey L., author; Rickard, Kathryn, advisor; Bloom, Larry J., committee member; Davalos, Deana, committee member; Anderson, Sharon, committee member (Colorado State University. Libraries, 2013)
Past literature has discussed gender differences in romantic partners' desires for intimacy and has suggested that these gender differences have negative effects on some relationships. Much of this literature has discussed heterosexual relationships. The current study sought to explore the validity of these claims within same-sex relationships. Participants completed surveys assessing their own desires for intimacy, their perceptions of their partners' desires for intimacy, and relationship outcome variables (satisfaction/commitment). Results indicated that perceived similarity to one's partner in overall desired intimacy is associated with relationship satisfaction and commitment. The effects of perceived similarity varied across types of intimacy, such that perceived similarity in desires for intellectual intimacy and recreational intimacy were most associated with relationship outcome variables, though slightly differently for men and women. The importance of direction of perceived discrepancy was also explored. Comparisons to previous research and implications for counseling and future research are discussed.
Keywords: couples; gender; GLBT; intimacy; relationships; similarity